Monte Carlo simulation of interferometric measurement and wavefront shaping under influence of shot noise and camera noise - Chunghyeong Lee; Jaeyeon Oh; Hakseok Ko; Mooseok Jang (JPhys Photonics)
Interferometry often serves as an essential building block of wavefront shaping systems to obtain optimal wavefront solutions. In this tutorial, we provide a Monte Carlo simulation tool to calculate the accuracy of interferometric measurements and its impact on wavefront shaping in the context of focusing through disordered media. In particular, we have focused on evaluating wavefront shaping fidelity under the influence of shot noise with practical considerations on the operation of digital image sensors, including readout noise, dark current noise, and digitization with finite bit-depth. Based on some exemplary simulation results, we provide practical guidance for setting up an interferometric measurement system for wavefront shaping applications.